Depression among elderlies with hypertension living in old folk homes, Indonesia - Indah Farida; Citra Windani Mambang Sari; Iwan Shalahuddin (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: Elderly will experience various degenerative diseases due to decreased bodily functions. The common suffered by the elderly is hypertension. Hypertension causes psychological problems in the elderly and following by depressed and afraid of the condition they are experiencing.Purpose: To determine the description of depression among the elderly people with hypertension living in old folk homesMethod : A quantitative with a design cross-sectional, the sample taken by a total sampling of 41 elderlies with hypertension. They were living in old folk homes Ciparay- west java under Indonesian Department of Social Welfare. Measurement tool using Geriatric Depression Scale (GDS) and screening by mini mental status examination (MMSE).Results: Finding of 10 elderlies (24.4%), without a symptom of depression, 24 (58.5%) had a mild depression, and 7 elderlies (17.1%) had a moderate depression.Conclusion: The most elderlies with hypertension can cause symptom of depression. Depressed and hypertensive in elderly, both symptoms need attention from management old folk home and health workers, to providing psychotherapy to help elderly hypertensive sufferers with depression change negative thought patterns or unproductive patterns that may as a trigger for the depression occurrence.